Evaluation of Novel Stereotactic Cannula for Stem Cell Transplantation against Central Nervous System Disease - Masahito Kawabori; Aki Tanimori; Shinri Kitta; Hideo Shichinohe; Kiyohiro Houkin (Hindawi Limited, 2020)
Cell therapy for central nervous system (CNS) disorders is beginning to prove its safety and efficiency. Intraparenchymal transplantation can be an option for cell delivery; however, one concern regarding this method is that the transplantation cannula may cause additional brain injuries. These include vessel damage, which results in brain hemorrhage, and clogging of the cannula by brain debris and/or cell clusters, which requires replacement of the cannula or forced injection causing jet flow of the cell suspension. We compared cannulas for cell delivery used in clinical trials, the Pittsburg and Mizuho cannulas, to a newly designed one, MK01, to assess their usability. MK01 has a spherical-shaped tip with a fan-like open orifice on the side of the cannula, which prevents vessel damage, clogging of brain debris, and jet flow phenomenon. We compared the extent of rat cervical and abdominal arterial damage with the cannula, the amount of debris in the cannula, the force needed to cause jet flow, and cell viability. While the viability of cells passed through the cannulas was almost the same among cannulas (approximately 95%), the Pittsburg cannula caused cervical arterial injury and subsequent hemorrhage, as it required a significantly smaller force to penetrate the arterial wall. Moreover, the Pittsburg cannula, but not the Mizuho and MK01 cannulas, showed high frequency of brain debris in the needle tip (approximately 80%) after brain puncture. While jet flow of the injection liquid was observed even when using smaller forces in the Pittsburg and Mizuho cannulas, MK01 constantly showed low jet flow occurrence. Thus, MK01 seems to be safer than the previously reported cannulas, although further investigation is necessary to validate its safety for clinical use.